Gephyrin-Independent GABA(A)R Mobility and Clustering during Plasticity - Niwa, Fumihiro (Public Library of Science, 2012)
The activity-dependent modulation of GABA-A receptor (GABA(A)R) clustering at synapses controls inhibitory synaptic transmission. Several lines of evidence suggest that gephyrin, an inhibitory synaptic scaffold protein, is a critical factor in the regulation of GABA(A)R clustering during inhibitory synaptic plasticity induced by neuronal excitation. In this study, we tested this hypothesis by studying relative gephyrin dynamics and GABA(A)R declustering during excitatory activity. Surprisingly, we found that gephyrin dispersal is not essential for GABA(A)R declustering during excitatory activity. In cultured hippocampal neurons, quantitative immunocytochemistry showed that the dispersal of synaptic GABA(A)Rs accompanied with neuronal excitation evoked by 4-aminopyridine (4AP) or N-methyl-D-aspartic acid (NMDA) precedes that of gephyrin. Single-particle tracking of quantum dot labeled-GABA(A)Rs revealed that excitation-induced enhancement of GABA(A)R lateral mobility also occurred before the shrinkage of gephyrin clusters. Physical inhibition of GABA(A)R lateral diffusion on the cell surface and inhibition of a Ca(2+) dependent phosphatase, calcineurin, completely eliminated the 4AP-induced decrease in gephyrin cluster size, but not the NMDA-induced decrease in cluster size, suggesting the existence of two different mechanisms of gephyrin declustering during activity-dependent plasticity, a GABA(A)R-dependent regulatory mechanism and a GABA(A)R-independent one. Our results also indicate that GABA(A)R mobility and clustering after sustained excitatory activity is independent of gephyrin.